2018
DOI: 10.1016/j.pneurobio.2018.04.007
|View full text |Cite
|
Sign up to set email alerts
|

The role of inflammation in subventricular zone cancer

Abstract: The adult subventricular zone (SVZ) stem cell niche has proven vital for discovering neurodevelopmental mechanisms and holds great potential in medicine for neurodegenerative diseases. Yet the SVZ holds a dark side - it can become tumorigenic. Glioblastomas can arise from the SVZ via cancer stem cells (CSCs). Glioblastoma and other brain cancers often have dismal prognoses since they are resistant to treatment. In this review we argue that the SVZ is susceptible to cancer because it contains stem cells, migrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 224 publications
(298 reference statements)
0
17
0
Order By: Relevance
“…As discussed above, stem cells are scarce in the adult brain and can only grow in protective stem cells niches, including the hippocampus and the SVZ [31,32]. These NSCs already possess the ability to proliferate and thus they could transform more easily and rapidly into BTPCs than any other post-mitotic neural cell in the brain [99]. After certain variations, neural precursor cells could become BTPCs (Figure 2).…”
Section: Cancer Stem Cellsmentioning
confidence: 99%
“…As discussed above, stem cells are scarce in the adult brain and can only grow in protective stem cells niches, including the hippocampus and the SVZ [31,32]. These NSCs already possess the ability to proliferate and thus they could transform more easily and rapidly into BTPCs than any other post-mitotic neural cell in the brain [99]. After certain variations, neural precursor cells could become BTPCs (Figure 2).…”
Section: Cancer Stem Cellsmentioning
confidence: 99%
“…To better address the clinical practice of patients with GBM, we should have a comprehensive understanding of predictive factors and prognostic potential of different progression patterns, especially for non-local failure. There is increasing evidence that the subventricular zone (SVZ) may be involved in the progression of GBM, because the dysregulated neural stem cells of SVZ can leave the niche and migrate over long distances, and finally contribute to the oncogenesis (11,12). Numerous studies have shown that patients whose lesions involved the SVZ have worse clinical outcomes and more aggressive patterns of recurrence (13,14).…”
Section: Introductionmentioning
confidence: 99%
“…We found that those GBM patients with higher PHQ-9 and GAD-7 score have significantly worse prognosis than their lower scored counterparts. It seems the case that glioblastoma and depressive/anxiety disorder share some common etiological factors, such as inflammation [ 33 , 34 ], neurotransmitter metabolism [ 35 ], glutamine [ 36 , 37 ], neural plasticity [ 38 , 39 ], etc. Nevertheless, none of these factors were confirmed by further research.…”
Section: Discussionmentioning
confidence: 99%